Anti-neuroinflammatory and antioxidant phenylpropanoids from Chinese olive. (15th July 2019) - Zhang, Shujuan; Huang, Yuying; Li, Yang; Wang, Yihai; He, Xiangjiu
Graphical abstract: Highlights: Bioactive phytochemicals of Chinese olive were conducted. Nineteen phenylpropanoids, including three novels, were isolated from Chinese olive. Some phenylpropanoids showed pronounced anti-neuroinflammatory, antioxidant and antidiabetic activities. Chinese olives could be served as a healthy product for neuroinflammatory related diseases. Abstract: Chinese olive is served as a famous fruit and traditional herb in China. In this study, the anti-neuroinflammatory and antioxidant phytochemicals of Chinese olive fruits were investigated. Three new phenylpropanoids (2, 6, 19 ), together with sixteen known congeners, have been isolated and identified. A variety of bioactivities related to the traditional healthy benefits of Chinese olive, including anti-neuroinflammatory, antioxidant and antidiabetic, have been evaluated for the identified compounds. The phenylpropanoids could significantly inhibit the production of nitric oxide induced by lipopolysaccharide (LPS) in microglia cells (BV-2). Compounds2, 6, and19 could dose-dependently reduce the expression levels of pro-inflammatory mediator iNOS and COX-2 expressions induced by LPS in BV-2 cells. Meanwhile, some phenylpropanoids showed remarkable antioxidant and antidiabetic activities. This study suggested that Chinese olive could be served as a healthy product for neuroinflammatory related diseases, such as Alzheimer's disease.